Hubungan Kunjungan Antenatal, Pertolongan Persalinan, dan Kunjungan Nifas dengan KB Pasca Persalinan di Provinsi Jawa Timur - Arina Rahmahanti Setiawan (Universitas Airlangga, 2024)
Background: Birth control is achieved through community participation in family planning programs. Program to increase the coverage of postpartum family planning is very beneficial to be applied in efforts to improve the health of mothers, children, and their families. Objectives: The aim of this research is to analyze factors related to postpartum family planning coverage in East Java Province. Methods: This research was an observational analytical research. The approach used in this research was a cross-sectional approach. The population in this research was all regency/ city in East Java based on the East Java Health Profile in 2021. The sample in this research used the total population of all regencies/cities in East Java Province with 38 regencies/ cities. Data analysis used Spearman’s correlation. Results: The results showed that the relation between first antenatal visits and postpartum family planning coverage obtained p=0.003 (p<0.05), the correlation between last antenatal visits and postpartum family planning coverage found p=0.068 (p>0.05), the correlation between childbirth assistance by health workers and postpartum family planning coverage found p=0.012 (p<0.05), the correlation between childbirth assistance at health service facilities and postpartum family planning coverage found p=0.012 (p<0.05), the correlation between first postpartum visit and postpartum family planning coverage found p=0.012 (p<0,05), the correlation between second postpartum visit and postpartum family planning coverage obtained p=0.005 (p<0.05), the correlation between third postpartum visit and postpartum family planning found p=0.001 (p<0.05). Conclusions: There is a relationship between antenatal visits, childbirth assistance, and postpartum visits to postpartum family planning coverage in East Java Province. Health providers should be encouraged to offer better counseling because it can impact women's decisions to utilize postpartum family planning.